Deskbound : standing up to a sitting world - Starrett, Kelly, ....-; Starrett, Juliet, ....-; Cordoza, Glen, ....- (Las Vegas (Nev.) : Victory Belt Publishing, 2016)
Youd better stand up for this bit of news. Sitting can wreak havoc on your health, and not just in the form of minor aches and pains. Recent studies show that too much sitting contributes to a host of diseasesfrom obesity and diabetes to cancer and depressionandliterally shortens your life. The facts are in: your chair is your enemy, and it is murdering your body. InDeskbound, Dr. Kelly Starrettphysical therapist and author of the New York Times andWall Street Journal bestselling book Becoming a Supple Leopardunveils how your sedentary lifestyle is killing you and, more important, what you can do to change it.Deskbound offers a detailed battle plan for surviving the chair and reclaiming your birthright of mobility and freedom from pain. It provides creative solutions to reduce the amount of time you spend perched on your backside, as well as strategies for the workplace and school that will improve your productivity and your overall health. You will learn how to identify and fix poor posture while sitting and standing; how to prevent, treat, and resolve low back, neck, shoulder, and wrist pain; and avoid and reverse repetitive stress injuries like carpal tunnel and tendonitis. Whether your goal is to maximize your performance in and out of the workplace or simply to live pain free,Deskbound is the blueprint. Dr. Starrett provides a revolutionary cure for desk-death.